Effect of Linum Usitatissimum and Sesamum Indicum Extract as Growth Promotors a Diets of Fingrlings of Ctenpharyngodon Idella - Ali, Sajid; Ashraf, Muhammad; Javid, Arshad; Khan, Noor; Rehman, Hafeez ur; Abbas, Sumaira; Mehmood, Ehsan (Journal of Basic and Emerging Sciences, 2024)
A 90-day feeding trial was designed to investigate the effects of dietary supplementation of Linum usitatissimum seed extract and Sesamum indicum seed extract on hematological traits and growth of fingerlings Labeo rohita. Fish were housed in cemented rectangular tanks at stocking density of 130 mg L-1 of water. There were three treatments and a control group. Control diet contained 32% protein and was composed of conventional ingredients. 1 % of the total ingredients were replaced with Linum usitatissimum seed extract in treatment 1 and 2% with Sesamum indicum seed extract in treatment 2 respectively. Treatment 3 composed of 96% of control diet + 2% Linum usitatissimum and 2% Sesamum indicum seed extract. Feed was offered to fish @ 2% of its body weight. Initial and final weight of Labeo rohita fingerlings was 7.33, 15.98g in control, 7.14 , 17.38 g in T1, 7.27 , 16.49 g in T2 and 7.30, 16.86 g in T3 respectively. All treatments showed better growth than control but treatment composed of linseed oil in diet showed significantly higher growth. Hematological studies showed increased levels of Hemoglobin, Platelets, TLC, RBCs, HCT, WBCs, and MCH in treatments while the level of Lymphocytes & MCV decreased as compared to control diet. Fish fed diet with 2% linseed extract in feed showed highest weight gain (10.24g) best F.C.R (1.28) and good hematological results suggesting that Linum usitatissimum seed extract is better option to include in future feed formulations for Ctenopharyngodon idella.